The family climate and its relationship to the future anxiety among high school students - Alanazi, Bandar Alaswad; Alghamdi, Saleh Yahya (Journal of Educational and Psychological Sciences, 2021)
This research aims to identify the relation between the family climate and the future anxiety among high school students. The researcher used the descriptive correlative approach for his research. Random sample of 210 high school students in Riyadh was chosen. The researcher used the family climate scale prepared by Kafafi (2010) and the future anxiety scale prepared by Ali (2013) and the research reached the following results: There is a statistically positive significant relationship on the level (0,01) between the family climate and the future anxiety among high school students. There are more frequent dimensions in the family climate among high school students like dehumanization which comes first then comes merged family and then comes affected love finally, comes unnatural family climate. There are no differences with any statistical significant concerning the future anxiety and the student's specialization in high school (scientific – theoretical). There is a statistical significant differences concerning the family climate in high school in favor of the Art students. The researcher presented a set of recommendations, including educating parents about the importance to provide a good family climate for their children, through which they can practice their normal lives and take care of their studies. He also recommends conducting preventive counseling programs from the effects of future anxiety for high school students in general and theoretical majors in particular, and he recommends not placing children before specific future options. Rather, giving them the necessary information, giving them the freedom to choose, and helping them if necessary, and finally, the researcher recommends contributing to other studies related to the future effects of future anxiety and linking it to other variables that may contribute to reducing anxiety and achieving mental health for individuals.
Keywords: family climate; future anxiety; high school students